Women and Poverty in Industrialized Countries - Wright, Robert E. (Journal of Income Distribution®, 1996)
This paper examines empirically the relationship between gender and poverty in eleven industrialized countries that form part of the Luxembourg Income Study. For each of these countries, Foster-Greer-Thorbecke poverty rates, based on a relative poverty line, are calculated separately for men and women. The overall poverty rate for adult men and women is decomposed into male and female poverty shares. These poverty shares are compared to the relative population shares of men and women. The main conclusion is that when the poverty experience of all women is compared to the poverty experience of all men, women are over-represented amongst the poor in some countries and under-represented amongst the poor in others. The latter part of this conclusion is in sharp disagreement with conventional views about the relationship between gender and poverty in industrialized countries.